EFETIVIDADE DO ASCORBATO DE SÓDIO 35% NA RESISTÊNCIA DE UNIÃO AO ESMALTE DE DENTES CLAREADOS - Coppla, Fabiana Fernandes Madalozzo (2014)
It is considered that the use of antioxidants may improve decreased enamel bond strength (BS) values after bleaching. The aim of this in vitro study was to evaluate the effectiveness of a 35%sodium ascorbate solution (SA), varying its application,(2-5 min or 3-1min applications) on bleached enamel BS values after with 10%, 16% or 22% carbamide peroxide (CP) or 35% hydrogen peroxide (HP). It was used 130 enamel surfaces of freshly extracted human molars, divided into 13 groups(n=10), according to the different treatments: G1:CP 10% + SA 35% 2-5 min; G2:CP 10% + SA 35% 3-1 min; G3:CP 10% without SA; G4:CP 16% + SA 35% 2-5 min; G5:CP 16% + SA 35% 3-1 min; G6: CP 16% without SA; G7:CP 22% + SA 35% 2-5 min; G8:CP 22% + SA 35% 3-1 min; G9:CP 22% without SA; G10:HP 35% + SA 35% 2-5 min; G11:HP 35% +SA 35% 3-1 min; G12:HP 35% without SA; G13:control group (without bleaching). Composite cylinders of 0.7 mm diameter x 1.2 mm high were made with Filtek Z350 composite, bonded with Scotchbond MP adhesive system. Microshear test was performed in an universal testing machine (Kratos) at a cross-head speed of 1mm/min. BS values were statistically evaluated using two tests: 1) two-way ANOVA and Tukey’s post-test (α=0.05) and 2) one-way ANOVAand Dunnett’s post-test (α=0.05). The results showed a significant decrease of BS values in immediate (G3:21,1 ± 4,0; G6:23,0 ± 2,1; G9:16,3 ± 2,6; G12:18,0 ± 3,4) compared to controls (G13:34,0 ± 5.3). Increased BS values were observed in allhydrogen peroxide groups, regardless of the AS application technique (G1:34,4 ± 4,1; G2:28,1 ± 4,6; G4:38,7 ± 3,0; G5: 32,6 ±3,0; G7: 18,9 ± 2,6; G8:30,4 ± 4,8; G10:29,8 ± 1,8; G11:38,6 ± 3,5). It was concluded that the use of 35% sodium ascorbate is an efficient strategy for reversing the impaired enamel bond strength after bleaching.